A Review of the Suitability of some Commonly Occurring Grasses of U.p. for the Production of Bleachable-grade Pulps - Dhawan, Rita; Karira, B. G.; Mathur, G. M. (Indian Forester, 1992)
Investigations carried out at F.R.I. on the production of bleachable grade pulps suitable for cultural papers from some commonly occurring grass species of U.P. have been described. The results have been summarized in terms of chemical composition, fibre dimensions and physical strength properties of pulps under optimum conditions. The results of pilot plant investigations carried out on mixture of grasses suitable for papermaking have also been included.